TINJAUAN PEMANFAATAN BEASISWA BIDIKMISI DALAM KEBERLANGSUNGAN STUDI MAHASISWA DI FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 420-427 , Wellya Rahma Nesya (Universitas Negeri Padang, 2014)
ABSTRACT The Bidikmisi scholarship is a scholarship which sponsored by the Directorate Higher Education of Indonesian Government. The scholarship is honored students who have the best achievement but poor. For continuing payment of Bidikmisi scholarship needs the best achievement with GPA (Grade Point Average) not less than 2,75. Now, in fact there are many students who got GPA under 2,75. The main purpose of this research to know the grade usage of Bidikmisi scholarship by the students of Engineering Faculty, State University of Padang. The method of research is descriptive quantitative and adopt the Guttman scale in analyzing. The number of respondents are 68 respondents. The results are about 19.1%, 79.9% used this scholarship for educational cost and living expenses, respectively. As much as 50,04% students used the scholarship budget for both living expenses and educational cost but still not optimum. Keywords : Grade Point Average, Bidikmisi Scholarship, Descriptive quantitative